Fragments d’un récit de voyage dans la Relation (1654) de Marie de l’Incarnation - Bonesso, Amandine (Ponti/Ponts, 2022)
his contribution examines the account of the missionary experience in New France that the Ursuline Marie de l’Incarnation (Tours, 1599 – Quebec City, 1672) gave in the spiritual autobiography, the Relation of 1654, which she wrote in Quebec City, where she had founded the first Ursuline monastery and the first women’s school institute in the New World some fifteen years earlier. The Relation, which is part of one of the practices of the direction of consciousness of the time and which is inspired by the hagiographic model, appears to be an original work insofar as the features of a mystical discourse are intertwined with some aspects of viatical writing. The generic crossbreeding is achieved through deviations from the enunciative norm of spiritual autobiography and through the feminine adaptation of discursive strategies and themes that characterise the texts of travellers and missionaries in America between the 16th and 17th centuries. Marie de l’Incarnation’s account of her missionary experience leads us to rethink the viaticum production of the period from a gender perspective.